Spontaneous intracerebral hemorrhage: A pediatric case of undetermined etiology and review of literature - Pulivarthi, Swaroopa; Rodriguez, Gustavo J.; Bershad, Eric M.; Mckinney, Alexander; Divani, Afshin A. (Journal of Pediatric Neuroradiology, 2013)
Cerebrovascular disorders, particularly intracerebral hemorrhage (ICH), rarely occur in children. The most common underlying cause for ICH in the pediatric population is arteriovenous malformation (AVM). The best approach to diagnostic evaluation of pediatric ICH is unknown due to its low incidence (2–3/100,000 children). In recent years, early discovery of underlying cause of pediatric ICH has been possible due to a more widespread use of imaging modalities such as computed tomography (CT), magnetic resonance imaging (MRI) and digital subtraction angiography (DSA). We report a case of a 5-year-old boy with a ICH of unknown etiology. He presented with left hemiparesis and left facial droop for one hour. Non-contrast CT scan demonstrated right periventricular hematoma extending to all ventricles. Follow-up MRI, CT angiography and DSA were unremarkable. Laboratory findings including liver function tests, hematologic studies were normal. Screening for hemoglobinopathies was negative. Transthoracic echocardiography was unremarkable. Surgery for ventricular drain placement and intense physical therapy were performed. During the follow ups at 1 and 6 mo of initial admission, repeat brain MRI and magnetic resonance angiography were unremarkable.The complete diagnostic evaluation in children presenting with ICH of undetermined origin is critically important, but still the etiology may not be identified in some cases. AsAVMs are the most common cause of ICHin children andmay rarely regress following hemorrhage, our patient's normal follow-up imaging may be related to such a spontaneous thrombosis of an underlying AVM.
Keywords: Intracerebral hemorrhage; pediatric; etiology; stroke